Drug-drug interactions in pharmaceutical development (Wiley-interscience, 2008)
Drug-Drug Interactions in Pharmaceutical Development comprehensively reviews the relevant science, industrial practice, and regulatory agency positions on drug-drug interactions. It focuses on the evaluation of potential drug-drug interactions, allowing researchers to address risk factors before a drug is put to market. The book covers both clinical and nonclinical aspects for understanding drug-drug interactions as well as in vitro and in vivo studies for use in studying interactions at the drug discovery stage.